Republic of Korea : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting and auditing practices in the Republic of Korea (Korea). Korean Accounting Standards, which have been established by an independent standard setting body, the Korea Accounting Standards Board (KASB), are largely consistent with International Financial Reporting Standards (IFRS). Korean Auditing Standards, which have been established by the Korean Institute of Certified Public Accountants (KICPA), are a translation of the International Standards on Auditing. The statutory regulator's audit engagement reviews have been strengthened in the last few years. However, opportunities still exist for noncompliance with established accounting and auditing standards. The policy recommendations of this report focus on strengthening the monitoring and enforcement of established accounting, reporting, and auditing requirements.